Naturally occurring quaternary benzo[c]phenanthridine alkaloids selectively stabilize G-quadruplexes - Jarosova, Petra; Paroulek, Petr; Rajecky, Michal; Rajecka, Veronika; Taborska, Eva; Eritja, Ramon; Aviñó, Anna; Mazzini, Stefania; Gargallo, Raimundo; Taborsky, Petr (Physical chemistry chemical physics, 2018)
In this work, the interaction of six natural benzo[c]phenanthridine alkaloids (macarpine, sanguilutine, sanguirubine, chelerythrine, sanguinarine and chelirubine) with parallel and antiparallel G-quadruplex DNA structures was studied. HT22 corresponding to the end of human telomeres and the modified promoter oncogene c-kit21 and Pu22 sequences have been used. Spectroscopically-monitored melting experiments and fluorescence titrations, competitive dialysis and nuclear magnetic resonance spectroscopy were used for this purpose. The results showed that these alkaloids stabilized G-quadruplex structures in terms of increments of Tm values (from 15 to 25 °C) with high selectivity over duplexes and unfolded DNA. The mode of binding was mainly by stacking on the terminal G-tetrads with stoichiometries of 1 : 2 (DNA : ligand). The presence of non-specific electrostatic interactions was also observed. Overall, the results pointed to a strong stabilization of G-quadruplex structures by these alkaloids.